All-solid-state lithium ion battery and preparation method thereof

By using dry film-forming technology and co-pressure processing to prepare positive and negative electrode films, the problem of processing ultra-thin electrolyte layers in existing all-solid-state lithium-ion batteries has been solved, realizing all-solid-state lithium-ion batteries with high energy density and stable interface contact.

CN121097231APending Publication Date: 2025-12-09SHENZHEN GUYAN NEW MATERIAL TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511110908.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-08
Publication Date
2025-12-09

AI Technical Summary

Technical Problem

Existing all-solid-state lithium-ion batteries face processing challenges in manufacturing ultra-thin electrolyte layers, leading to poor interface contact and battery failure.

Method used

A dry membrane fabrication technique is used to prepare positive electrode membrane, negative electrode membrane and electrolyte membrane. Then, they are stacked and pressed to the required thickness through co-pressing, including co-rolling, co-rolling, co-hot pressing or co-extrusion, to solve the problems of difficulty in making the electrolyte layer thin and poor interface contact.

Benefits of technology

The processing of ultra-thin electrolyte layers has been achieved, which improves the energy density and interface contact quality of all-solid-state lithium-ion batteries and simplifies the production process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121097231A_ABST
    Figure CN121097231A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of all-solid-state lithium ion batteries, and discloses an all-solid-state lithium ion battery and a preparation method thereof.The preparation method comprises the following steps that a positive electrode membrane, a negative electrode membrane and an electrolyte membrane are prepared through a dry-method membrane preparation technology; stacking the prepared positive electrode membrane, the prepared negative electrode membrane and the prepared electrolyte membrane according to the sequence of the positive electrode membrane, the electrolyte membrane and the negative electrode membrane; and carrying out co-pressing treatment on the stacked positive electrode membrane, electrolyte membrane and negative electrode membrane to obtain the all-solid-state lithium ion battery with the required thickness. The positive electrode membrane, the negative electrode membrane and the electrolyte membrane which are prepared in advance are stacked together, and then the all-solid-state lithium ion battery is continuously co-pressed to a certain thickness in a co-pressing treatment manner, so that the problems that the electrolyte is difficult to thin and the interface contact is poor are solved at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of all-solid-state lithium ion batteries, and particularly relates to an all-solid-state lithium ion battery and a preparation method thereof. BACKGROUND

[0002] All-solid-state batteries are considered as the core direction of the next generation of energy storage technology due to their high energy density and intrinsic safety (compared with traditional liquid lithium ion batteries). Among them, the dry manufacturing process has the significant advantages of environmental friendliness, low energy consumption and process simplification due to the complete elimination of toxic organic solvents, and becomes an important path to realize the large-scale sustainable production of all-solid-state batteries. However, the current dry manufacturing process has serious bottlenecks in manufacturing thin electrolyte films and constructing stable electrode / electrolyte interfaces, which hinders its practical application. The main problems are: to achieve high energy density, an ultrathin electrolyte layer (thickness less than or equal to 50 μm) is needed, but the ultrathin electrolyte layer faces the problem of difficult processing, mainly in the processes of manufacturing, cutting, transferring, etc. In addition, due to the reliance on solid phase for ion and electron transmission, poor interface contact can easily lead to battery failure or failure problems.

[0003] Therefore, the prior art still needs to be improved and developed. SUMMARY

[0004] In view of the deficiencies of the prior art, the present application provides an all-solid-state lithium ion battery and a preparation method thereof, so as to solve the problem that the electrolyte layer in the existing all-solid-state lithium ion battery is difficult to be thin (thickness less than or equal to 50 μm).

[0005] The technical scheme adopted by the present application to solve the above technical problems is as follows:

[0006] In a first aspect of the present application, a preparation method of an all-solid-state lithium ion battery is provided, and the preparation method comprises the following steps:

[0007] The positive electrode film, the negative electrode film and the electrolyte film are prepared by using a dry film preparation technology;

[0008] The prepared positive electrode film, negative electrode film and electrolyte film are stacked in the order of positive electrode film, electrolyte film and negative electrode film;

[0009] The stacked positive electrode film, electrolyte film and negative electrode film are subjected to co-pressing treatment to obtain an all-solid-state lithium ion battery with a desired thickness.

[0010] Preferably, the temperature of the co-pressing treatment is 50-150℃.

[0011] Preferably, the processing speed of the co-pressing treatment is 0.1-5 m / s.

[0012] Preferably, the co-pressing process is co-rolling, co-rolling, co-hot pressing, co-cold pressing or co-extrusion.

[0013] Preferably, the desired thickness is 40-450 μm.

[0014] Preferably, the positive electrode film comprises a positive electrode active material, a binder and a conductive agent.

[0015] Preferably, the electrolyte film comprises an electrolyte material and a binder.

[0016] Preferably, the negative electrode film comprises a negative electrode active material, a binder and a conductive agent.

[0017] In a second aspect of the present application, a full solid-state lithium ion battery is provided, which is prepared by the preparation method described above.

[0018] Advantages:

[0019] The present application discloses a full solid-state lithium ion battery and a preparation method thereof. BRIEF DESCRIPTION OF DRAWINGS

[0020] Figure 1 A flow chart of a preparation method of a full solid-state lithium ion battery in a preferred embodiment of the present application.

[0021] Figure 2 A co-rolling schematic diagram in a preferred embodiment of the present application.

[0022] Figure 3 A co-rolling schematic diagram in a preferred embodiment of the present application.

[0023] Figure 4 A co-extrusion schematic diagram in a preferred embodiment of the present application.

[0024] Figure 5 An SEM image of a sample prepared in Example 1 of the present application.

[0025] Figure 6 An SEM image of a sample prepared in Example 2 of the present application.

[0026] Figure 7 An SEM image of a sample prepared in Example 3 of the present application.

[0027] Figure 8 An SEM image of a sample prepared in Example 4 of the present application.

[0028] Figure 9SEM images were prepared for the sample of Example 5 of the present application.

[0029] Figure 10 SEM images were prepared for the sample of Example 6 of the present application.

[0030] Figure 11 SEM images were prepared for the sample of Example 7 of the present application.

[0031] Figure 12 SEM images were prepared for the sample of Example 8 of the present application.

[0032] Figure 13 SEM images were prepared for the sample of Comparative Example 1 of the present application.

[0033] Figure 14 SEM images were prepared for the sample of Comparative Example 2 of the present application. DETAILED DESCRIPTION

[0034] The present application provides a full solid-state lithium ion battery and a preparation method thereof, in order to make the purpose, technical scheme and effect of the present application more clear and explicit, the present application is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0035] At present, there is no good solution for how to make the electrolyte layer of the full solid-state lithium ion battery thin, and it is difficult to continuously produce by applying ultra-high pressure to the stacked full solid-state lithium ion battery to solve the interface problem.

[0036] Based on this, the present application provides a preparation method of a full solid-state lithium ion battery, as shown in Figure 1 , the preparation method comprises the following steps:

[0037] The positive electrode film, the negative electrode film and the electrolyte film are prepared by using a dry film preparation technology;

[0038] The prepared positive electrode film, negative electrode film and electrolyte film are stacked in the order of positive electrode film, electrolyte film and negative electrode film;

[0039] The stacked positive electrode film, electrolyte film and negative electrode film are co-pressed to obtain a full solid-state lithium ion battery with a desired thickness.

[0040] The present application solves the problems of difficulty in making the electrolyte thin and poor interface contact by stacking the pre-designed positive electrode film, negative electrode film and electrolyte film together, and then co-pressing the full solid-state lithium ion battery to a certain thickness by co-pressing.

[0041] In addition, it should be noted that, in order to achieve the above technical effects, only the negative electrode film and the electrolyte film can be co-pressed, and then stacked with the positive electrode film; or the positive electrode film and the electrolyte film can be co-pressed, and then stacked with the negative electrode; or the desired material can be co-pressed with a medium with good ductility to obtain an ultra-thin film, and then transferred to the positive electrode film, the electrolyte film and the negative electrode film to realize the use of the ultra-thin film.

[0042] In some embodiments, the co-pressing temperature is 50-150℃.

[0043] If the co-pressing temperature is too low, it is not conducive to the movement of the binder fibers in the negative electrode film, the positive electrode film and the electrolyte film. The higher the temperature, the better the flexibility of the negative electrode film, the positive electrode film and the electrolyte film, but it cannot be higher than the temperature that the negative electrode film, the positive electrode film and the electrolyte film can withstand. In addition, the temperature used is different according to the type of the binder.

[0044] In some embodiments, the processing speed of the co-pressing is 0.1-5m / s.

[0045] If the processing speed is slow, it will affect the efficiency, and if the processing speed is too fast, it may cause the negative electrode film, the positive electrode film and the electrolyte film to break.

[0046] In some embodiments, the co-pressing is co-rolling, co-rolling, co-heat pressing, co-cold pressing or co-extrusion.

[0047] Through co-rolling, co-rolling and other methods, pressure can be provided to the negative electrode film, the positive electrode film and the electrolyte film. The negative electrode film, the positive electrode film and the electrolyte film deform under the action of pressure. The co-rolling, co-rolling and other methods limit the direction of deformation of the negative electrode film, the positive electrode film and the electrolyte film, so that the negative electrode film, the positive electrode film and the electrolyte film can only deform in the direction of becoming thinner. Among them, the co-rolling schematic diagram is shown in Figure 2 , the co-rolling schematic diagram is shown in Figure 3 , and the co-extrusion schematic diagram is shown in Figure 4 .

[0048] The best co-pressing method is co-rolling, and the specific method is to use three or more levels of rollers, and the temperature of each roller increases with the base of the roller. For example, the first roller is 80℃, the second roller is 120℃, the third roller is 120℃, the fourth roller is 90℃, and the processing speed is 0.8m / s.

[0049] In some embodiments, the desired thickness is 40-450μm.

[0050] In some preferred embodiments, the desired thickness is 50-200μm.

[0051] In some embodiments, the positive electrode film comprises a positive electrode active material, a binder and a conductive agent.

[0052] In some embodiments, the electrolyte film comprises an electrolyte material, a binder.

[0053] In some embodiments, the negative electrode film comprises a negative electrode active material, a binder, a conductive agent.

[0054] The preparation method of the present application has more advantages in realizing higher energy density full solid-state lithium ion batteries, such as full solid-state lithium ion batteries with silicon as the negative electrode. Specifically, it is well known that silicon negative electrodes face serious volume change problems during the charging and discharging process of full solid-state lithium ion batteries, and reducing the thickness of the negative electrode can alleviate a series of adverse effects caused by volume change, while shortening the ion and electron transmission path.

[0055] The embodiment of the present application provides a full solid-state lithium ion battery prepared by the above preparation method.

[0056] The preparation method of the present application is suitable for the following applications:

[0057] (1) Full solid-state lithium ion battery:

[0058] Positive electrode: layered oxide (including LiCoO2, LiNi x Co y Mn Z O2(x+y+z=1), LiNi x Co y Al z O2(NCA)), polyanion compound (LiFePO4, LiMn x Fe 1-x PO4(0<x<1)), spinel oxide (LiMn2O4).

[0059] Electrolyte: sulfide-based (Li3PS4, Li7P3S 11 , Li 10 GeP2S 12 , Li 3.833 Sn 0.867 S4, Li 6-y PS 5-y X 1+y , wherein X is one or more of Cl, Br, I, and F, and y is in the range of 0-2.0), oxide-based (Li7La3Zr2O 12 , Li 1.3 Al 0.3 Ti 1.7 (PO4)3), polymer-based (such as PEO, PVDC, PVDF, PMGDA, PMMA, etc.).

[0060] Negative electrode: graphite-based, alloy (SiOx / C).

[0061] (2) All-solid-state sodium-ion battery:

[0062] Positive electrode: Layered oxide (Na) x Ni a Fe b Mn c M d O2 (a+b+c+d=1, 0.7≤x≤1.0, where M is a doping element such as K, Li, Ca), Prussian blue analogues, and polyanionic compounds (Na3V2(PO4)3, etc.).

[0063] Electrolytes: sulfide-based, oxide-based.

[0064] Negative electrode: hard carbon, titanium-based compounds.

[0065] (3) All-solid-state potassium-ion battery:

[0066] Positive electrode: Prussian blue analogue, fluorooxalate.

[0067] Electrolyte: Polymer-based.

[0068] Negative electrode: graphite-based, organic negative electrode (perylenetetracarboxylic acid dianhydride, conjugated dicarboxylate).

[0069] Other battery systems include: hybrid ion batteries (sodium-potassium), solid-state metal batteries (lithium-sulfur, lithium-air batteries), and multivalent metal ion batteries (such as magnesium and zinc).

[0070] In addition, the binders used for the positive electrode, negative electrode, and electrolyte include, but are not limited to: polytetrafluoroethylene binders, polyolefin binders (such as maleic anhydride modified polypropylene), styrene-butadiene rubber-based binders, and ethylene glycol-maleic ester copolymer binders.

[0071] Conductive agents used in the positive and negative electrodes include, but are not limited to: acetylene black, conductive carbon black, graphite, metal fibers, carbon nanofibers, carbon nanotubes (single-walled and multi-walled), and graphene.

[0072] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are merely some embodiments of the present invention, not all embodiments, and are intended only to illustrate the present invention and not to limit it. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0073] Example 1

[0074] The positive electrode film, the electrolyte film and the negative electrode film are prepared by dry film preparation technology.

[0075] The thickness of the positive electrode film, the electrolyte film and the negative electrode film is 200 μm, 100 μm and 70 μm respectively.

[0076] The prepared positive electrode film, the electrolyte film and the negative electrode film are stacked in the order of positive electrode film-electrolyte film-negative electrode film.

[0077] The stacked battery is subjected to three-stage roller pressing to obtain a co-pressed film with a thickness of 100 μm.

[0078] The temperature of the three-stage rollers is 100 ℃, 120 ℃ and 80 ℃ respectively, and the final roller linear speed is 2.0 m / s.

[0079] The co-pressed film is subjected to isostatic pressing at 500 MPa for 120 s to obtain the sample of Example 1.

[0080] The final total thickness of Example 1 is 68.56 μm, and the thickness of the electrolyte and the negative electrode is 18.73 μm and 19.62 μm respectively.

[0081] Example 2

[0082] The positive electrode film, the electrolyte film and the negative electrode film are prepared by dry film preparation technology.

[0083] The thickness of the positive electrode film, the electrolyte film and the negative electrode film is 500 μm, 150 μm and 100 μm respectively.

[0084] The prepared positive electrode film, the electrolyte film and the negative electrode film are stacked in the order of positive electrode film-electrolyte film-negative electrode film.

[0085] The stacked battery is subjected to four-stage roller pressing to obtain a co-pressed film with a thickness of 200 μm.

[0086] The temperature of the four-stage rollers is 100 ℃, 120 ℃, 120 ℃ and 75 ℃ respectively, and the final roller linear speed is 1.5 m / s.

[0087] The co-pressed film is subjected to isostatic pressing at 500 MPa for 120 s to obtain the sample of Example 2.

[0088] The final total thickness of Example 2 is 126.05 μm, and the thickness of the electrolyte and the negative electrode is 20.83 μm and 24.74 μm respectively.

[0089] Example 3

[0090] The positive electrode film, the electrolyte film and the negative electrode film are prepared by dry film preparation technology.

[0091] The thickness of the positive electrode film, the electrolyte film and the negative electrode film is 500 μm, 100 μm and 70 μm respectively.

[0092] The prepared positive electrode film, electrolyte film and negative electrode film were stacked in the order of positive electrode film-electrolyte film-negative electrode film.

[0093] The stacked battery was subjected to four-stage rolling to obtain a co-pressed film with a thickness of 150 μm.

[0094] The four-stage roller temperatures were 100 ℃, 125 ℃, 125 ℃ and 80 ℃, respectively, and the final roller linear velocity was 1.0 m / s.

[0095] The co-pressed film was subjected to isostatic pressing at 500 MPa for 120 s to obtain the sample of Example 3.

[0096] The final total thickness of Example 3 was 90.50 μm, and the electrolyte thickness and the negative electrode thickness were 14.02 μm and 17.86 μm, respectively.

[0097] Example 4

[0098] The positive electrode film, electrolyte film and negative electrode film were prepared by dry film forming technology.

[0099] The thicknesses of the positive electrode film, electrolyte film and negative electrode film were 300 μm, 150 μm and 70 μm, respectively.

[0100] The prepared positive electrode film, electrolyte film and negative electrode film were stacked in the order of positive electrode film-electrolyte film-negative electrode film.

[0101] The stacked battery was subjected to three-stage rolling to obtain a co-pressed film with a thickness of 150 μm.

[0102] The three-stage roller temperatures were 110 ℃, 110 ℃ and 100 ℃, respectively, and the final roller linear velocity was 1.2 m / s.

[0103] The co-pressed film was subjected to isostatic pressing at 500 MPa for 120 s to obtain the sample of Example 4.

[0104] The final total thickness of Example 4 was 91.44 μm, and the electrolyte thickness and the negative electrode thickness were 21.22 μm and 25.30 μm, respectively.

[0105] Example 5

[0106] The positive electrode film, electrolyte film and negative electrode film were prepared by dry film forming technology.

[0107] The thicknesses of the positive electrode film, electrolyte film and negative electrode film were 400 μm, 200 μm and 100 μm, respectively.

[0108] The prepared positive electrode film, electrolyte film and negative electrode film were stacked in the order of positive electrode film-electrolyte film-negative electrode film.

[0109] The stacked battery is subjected to four-stage rolling to obtain a co-pressed film with a thickness of 200 μm.

[0110] The four-stage roller temperatures are 80℃, 120℃, 125℃, and 90℃, respectively. The final roller linear speed is 0.8 m / s.

[0111] The co-pressed film is subjected to isostatic pressing at 500 MPa for 120 s to obtain the sample of Example 5.

[0112] The final total thickness of Example 5 is 124.37 μm, and the electrolyte thickness and cathode thickness are 35.13 μm and 18.52 μm, respectively.

[0113] Example 6

[0114] The anode film, electrolyte film, and cathode film are prepared by dry film forming technology.

[0115] The thicknesses of the anode film, electrolyte film, and cathode film are 550 μm, 150 μm, and 100 μm, respectively.

[0116] The prepared anode film, electrolyte film, and cathode film are stacked in the order of anode film-electrolyte film-cathode film.

[0117] The stacked battery is subjected to four-stage rolling to obtain a co-pressed film with a thickness of 200 μm.

[0118] The four-stage roller temperatures are 100℃, 150℃, 150℃, and 90℃, respectively. The final roller linear speed is 0.4 m / s.

[0119] The co-pressed film is subjected to isostatic pressing at 500 MPa for 120 s to obtain the sample of Example 6.

[0120] The final total thickness of Example 6 is 126.18 μm, and the electrolyte thickness and cathode thickness are 19.49 μm and 21.79 μm, respectively.

[0121] Example 7

[0122] The anode film, electrolyte film, and cathode film are prepared by dry film forming technology.

[0123] The thicknesses of the anode film, electrolyte film, and cathode film are 400 μm, 150 μm, and 150 μm, respectively.

[0124] The prepared anode film, electrolyte film, and cathode film are stacked in the order of anode film-electrolyte film-cathode film.

[0125] The stacked battery is subjected to five-stage rolling to obtain a co-pressed film with a thickness of 200 μm.

[0126] The temperatures of the five rollers were 120℃, 150℃, 150℃, 100℃, and 70℃, respectively. The linear speed of the last roller was 0.5 m / s.

[0127] The co-pressed film was subjected to isostatic pressing at 500 MPa for 120 s to obtain the sample of Example 7.

[0128] The final total thickness of Example 7 was 126.88 μm, and the thicknesses of the electrolyte and the negative electrode were 24.20 μm and 30.14 μm, respectively.

[0129] Example 8

[0130] The positive electrode film, the electrolyte film, and the negative electrode film were prepared by using the dry film preparation technology.

[0131] The thicknesses of the positive electrode film, the electrolyte film, and the negative electrode film were 500 μm, 200 μm, and 120 μm, respectively.

[0132] The prepared positive electrode film, the electrolyte film, and the negative electrode film were stacked in the order of positive electrode film-electrolyte film-negative electrode film. The stacked battery was subjected to four-stage rolling to obtain a co-pressed film with a thickness of 200 μm.

[0133] The temperatures of the four rollers were 100℃, 120℃, 120℃, and 100℃, respectively. The linear speed of the last roller was 0.35 m / s.

[0134] The co-pressed film was subjected to isostatic pressing at 500 MPa for 120 s to obtain the sample of Example 8.

[0135] The final total thickness of Example 8 was 127.36 μm, and the thicknesses of the electrolyte and the negative electrode were 31.20 μm and 24.62 μm, respectively.

[0136] Comparative Example 1

[0137] The positive electrode film, the electrolyte film, and the negative electrode film were prepared by using the dry film preparation technology.

[0138] The thicknesses of the positive electrode film, the electrolyte film, and the negative electrode film were 100 μm, 200 μm, and 150 μm, respectively.

[0139] The prepared positive electrode film, the electrolyte film, and the negative electrode film were stacked in the order of positive electrode film-electrolyte film-negative electrode film.

[0140] The stacked film material was subjected to isostatic pressing at 500 MPa for 120 s.

[0141] The obtained sample was Comparative Example 1, and the final total thickness was 205.27 μm, and the thicknesses of the electrolyte and the negative electrode were 67.86 μm and 69.59 μm, respectively.

[0142] Comparative Example 2

[0143] The positive electrode film, the electrolyte film and the negative electrode film are prepared by dry film forming technology.

[0144] The thickness of the positive electrode film, the electrolyte film and the negative electrode film is 70 μm, 150 μm and 100 μm respectively.

[0145] The prepared positive electrode film, the electrolyte film and the negative electrode film are stacked in the order of positive electrode film-electrolyte film-negative electrode film.

[0146] The stacked film material is subjected to 500 MPa, 120 s isostatic pressing.

[0147] The obtained sample is Comparative Example 1, and the final total thickness is 173.27 μm, and the electrolyte thickness and the negative electrode thickness are 68.36 μm and 73.74 μm respectively.

[0148] Among them, the electrolyte and negative electrode thickness comparison data of the samples obtained by Examples 1-8 and Comparative Examples 1-2 are shown in Table 1 below;

[0149] Table 1

[0150] Electrolyte thickness / pm Negative electrode thickness pm Comparative Example 1 67.86 69.59 Comparative Example 2 68.36 73.74 Example 1 18.73 19.62 Example 2 20.83 24.74 Example 3 14.02 17.86 Example 4 21.22 25.30 Example 5 35.13 18.52 Example 6 19.49 21.79 Example 7 24.20 30.14 Example 8 31.20 24.62

[0151] The SEM images of the samples prepared by Examples 1-8 and Comparative Examples 1-2 are shown in Figures 5-14 .

[0152] It should be understood that the application of the present application is not limited to the above examples, and those skilled in the art can make improvements or changes according to the above description, and all these improvements and changes shall belong to the protection scope of the appended claims of the present application.

Claims

1. A method for producing an all-solid-state lithium-ion battery, characterized by, The preparation method comprises the following steps: An anode film, a cathode film and an electrolyte film are prepared by using a dry film preparation technology; The prepared anode film, cathode film and electrolyte film are stacked in the order of the cathode film, electrolyte film and anode film; The stacked anode film, electrolyte film and cathode film are co-pressed to obtain a full solid-state lithium ion battery with a required thickness.

2. The method of producing an all-solid-state lithium-ion battery according to claim 1, characterized by, The co-pressing temperature is 50-150°C.

3. The method of claim 1, wherein the method further comprises: The co-pressing processing speed is 0.1-5 m / s. ​ 4. The method of claim 1, wherein the method further comprises: The co-pressing processing is co-rolling, co-rolling, co-hot pressing, co-cold pressing or co-extrusion.

5. The method of claim 1, wherein the method further comprises: The required thickness is 40-450 μm.

6. The method of claim 1, wherein the method further comprises: The cathode film comprises a cathode active material, a binder and a conductive agent.

7. The method of claim 1, wherein the method further comprises: forming a plurality of solid electrolyte layers on the substrate; and forming a plurality of cathode layers on the plurality of solid electrolyte layers. The electrolyte film comprises an electrolyte material and a binder.

8. The method of claim 1, wherein the method further comprises: The anode film comprises an anode active material, a binder and a conductive agent.

9. An all-solid-state lithium-ion battery, characterized by, The full solid-state lithium ion battery is prepared by using the preparation method in any one of claims 1-8.